Self-organized holonic multi-agent manufacturing system: the behavioural perspective - Barbosa, José (2014)
New manufacturing control architectures rely on the decentralization of the system entities to handle in a more effective way the current constraints imposed to the highly dynamic manufacturing world. Despite of their benefits, these architectures miss the performance levels of those achieved by traditional centralized systems running without failures. This paper proposes a holonic multi-agent system architecture, based on ADACOR foundations, which considers the self-organization concept to create a two vector solution embedded in micro and macro levels. The paper describes the self-organization mechanism embed at the micro level, named behavioural selforganization, being validated using the AIP-PRIMECA flexible manufacturing system.